Structure of enteric neurons. - Brehmer, Axel (Advances in Anatomy Embryology and Cell Biology, 2006)
The ENS contains numerous different neuron populations which belong to three main groups, primary afferent neurons, interneurons and effector neurons. The most extensive knowledge on the different enteric neuron types is derived from studies in the guinea pig. A significant obstacle for the transfer of this knowledge to putative equivalent enteric neurons of other species, including human, is species differences as to their morphological, chemical, physiological etc. phenotypes. Modern morphological classifications are based on the work of the Russian histologist Dogiel. Since the late 1970s, refined morphological classifications of enteric neurons beyond Dogiel have been attempted mainly in two species, the pig and the guinea pig. These reflect the immunohistochemical diversity of enteric neurons more precisely but are far from being complete. In this paper, we follow two aims. First, we have presented an overview on the chemical coding of the morphological neuron types described by Stach in the pig intestine. In doing so, we have pointed out the difference between the definitions of type I neurons given by Dogiel and Stach. Second, we have attempted to provide a basis for the morpho-chemical classification of human enteric neurons as revealed by their immunoreactivity for NFs and several neuroactive substances or related markers. According to results from guinea pig, where there is functional evidence, human morphological type II neurons (non-dendritic, multiaxonal; co-reactive for NF, CAR, SOM, SP) seem to be the intrinsic primary afferent neurons. This conclusion is based primarily on structural equivalence. Human ENK-positive, stubby (type I) neurons maybe ascending interor motorneurons. In contrast, nitrergic, VIP-reactive spiny (type I) neurons maybe descending inter- or motor neurons. Further, morphologically defined human neuron types, i.e. type III, type V and dendritic type II neurons, are non-nitrergic but could not be chemically defined as yet. Future investigations of morpho-chemical characteristics of human enteric neurons including also other cytoskeletal markers will provide a broader basis for neurohistopathological diagnostics of gut diseases.